Analysis Of Maturity Level Cloud Computing Service Provider Using COBIT 4.1 - Idhom, Mohammad; Alit, Ronggo; Fauzi, Akhmad (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This research is focused on the analysis of cloud computing service provision by both division IT Project and IT Support Division at PT. Eikon Technology in Surabaya to improve business process in this company, by examining the extent of cloud services provided by the company to customers through the two divisions by applying information technology. The total detailed control objective used was 38 detail controls performed by the IT Project division and 40 control details performed by the IT Support division. The result of this research is analysis of current and expected maturity level from sub domain PO4, PO7, DS1, DS5, and DS7, got the average total maturity level is 2.7 and the expected maturity level is 3.76. Recommendations and conclusions are expected to develop the process of information technology governance in the form of providing cloud computing services to better and efficient in supporting the business in PT Eikon Technology, Surabaya.Â Keywords : Cobit 4.1, Cloud Computing, IT Project, and IT Support.